PENINGKATAN KETERAMPILAN MENULIS TEKS BERITA PADA PELAJARAN BAHASA INDONESIA MENGGUNAKAN MEDIA FOTO PERISTIWA PADA SISWA KELAS VIII C SMP NEGERI 6 TAMBUSAI UTARA TAHUN PELAJARAN 2017/2018 - Islamidar Islamidar (STKIP Rokania Pasir Pangaraian, 2020)
This study aims to improve and enhance students 'writing skills, especially writing news texts, as well as motivating and fostering students' interest so that they are interested in taking part in learning to write news text using the event photo media. The method used is classroom action research. C SMP Negeri 6 Tambusai Utara, Rokan Hulu Regency. a total of 24 students Teacher observation results showed a good increase and change from the first cycle of the first meeting to the second cycle of the second meeting, namely from 71.1, 77.78, 86.66 to 93.33. Student learning outcomes show a good improvement and change from the first cycle of the first meeting to the second cycle of the second meeting, namely from 72.91, 76.37, 81.04 to reach 84.45. Teachers are expected to be able to continuously carry out learning activities by linking real problems to students using learning resources and preparing creative steps for learning.